Optimalisasi Peran Orang Tua dalam Internalisasi Nilai-Nilai Pendidikan Islam pada Generasi Alpha di Era Digital - Ayuningtiyas, Sukma; Rohmah Hayati, Nur (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The rapid development of digital technology has had a significant impact on the mindset, behavior, and character formation of Generation Alpha. Unlimited access to information not only provides benefits but also presents various moral and social challenges that must be anticipated. This condition requires parents to play an increasingly strategic role in internalizing Islamic educational values so that children are able to filter negative influences in the digital era. This study aims to examine and optimize the role of parents in instilling Islamic educational values in Generation Alpha. The method used is a qualitative approach, with data collection techniques including literature review and observation of Muslim family parenting patterns. The results of the study indicate that optimizing the role of parents can be achieved through role modeling, habituation of Islamic values in daily life, guidance in the use of digital technology, and intensive, open, and educational communication. With an optimal parental role, the internalization of Islamic educational values is expected to shape Generation Alpha into individuals who are religious, morally upright, critical, adaptive, and wise in utilizing digital technology responsibly